The Influence of Religious Work Ethic On Deviant Behaviour and Mediating Role of Ethical Atmosphere - Wahyudi, Amin (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aims at analyzing and determining the influence of religious workethic on deviant behaviour and mediating the role of ethical atmosphere.Thestudy design is a corelational research. The variables of this research aredeviant behaviour as the dependent variable, religious work ethic as anindependent variable and ethical atmosphere as the mediating variable. Thepopulation in this study were employees of government offices, universities,hospitals and schools in the region of Surakarta. The samples of this study are100 people participant with convenience sampling techniques. The researchinstrument used is questionnaire. The analysis applied in this research is pathanalysis with multiple linear regressions. Theoretically, this study is expectedto provide benefits in developing a model that describes the concept of thereligious work ethic with deviant behaviors of human resources in anorganization. Practically, this study is expected to give benefits in decisionmakingby the head of the institution that is the object of this research. Theresults show that there is a negative and significant influence religious workethics and ethics atmosphere on deviant behaviour, there is a positive andsignificant influence religious work ethic on ethical atmosphere. Theconclution of this study shows that religious work ethics and ethicalatmosphere are very important for the development of human resourcesbehaviorKeywords : Deviant Behaviour; Ethic Atmosphere; Religious Work Ethics,